Challenges and Extent of Readiness Among Teachers in the Implementation of the Kindergarten Curriculum in Select Public Elementary Schools in the Philippines - Cristie Ann L. Jaca (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study determined and analyzed the extent of readiness in the implementation of the kindergarten curriculum and the challenges encountered by teachers in public elementary schools in the Division of Cebu City, Philippines. It employed the mixed method using quantitative – qualitative technique. The study was conducted in DepEd’s Cebu City Division, with Kindergarten teachers and school heads that served as research-respondents who answered the adapted instrument on contextualizing Kindergarten curriculum. The gathered data were treated using descriptive and inferential statistics supported by thematic analysis. The study revealed that teachers are always ready on the implementation of the Kindergarten curriculum. Further, the study finds that there is a significant relationship between age, educational qualification, and years of teaching experience of teachers in the use of available materials. Furthermore, there is a significant difference on the school environment when grouped by its clustered district. The study concluded that the implementation of the contextualized Kindergarten curriculum based on availability of instructional materials, forms of learning, evaluation method of learners, and school environment were always made available for teachers to use. After the school heads’ answers were transcribed, coded, categorized and analyzed, there were three themes that came out namely: preparation time, development of instructional materials, and the need for teacher training. The implementation of the Kindergarten curriculum has received different feedback from teachers.  Their expressed challenges are categorized into: Language Difficulties, Preparation Time, and Instructional Materials Development.